Reduction of Leukocyte Microvascular Adherence and Preservation of Blood-Brain Barrier Function by Superoxide-Lowering Therapies in a Piglet Model of Neonatal Asphyxia - Ruden, Jacob B.; Quick, Kevin L.; Gonzales, Ernesto R.; Shah, Aarti R.; Park, T. S.; Kennedy, Nan; Dugan, Laura L.; Gidday, Jeffrey M. (Frontiers in Neurology, 2019)
Background: Asphyxia is the most common cause of brain damage in newborns. Substantial evidence indicates that leukocyte recruitment in the cerebral vasculature during asphyxia contributes to this damage. We tested the hypothesis that superoxide radical (O2•) promotes an acute post-asphyxial inflammatory response and blood-brain barrier (BBB) breakdown. We investigated the effects of removing O2• by superoxide dismutase (SOD) or C3, the cell-permeable SOD mimetic, in protecting against asphyxia-related leukocyte recruitment. We also tested the hypothesis that xanthine oxidase activity is one source of this radical. Methods: Anesthetized piglets were tracheostomized, ventilated, and equipped with closed cranial windows for the assessment of post-asphyxial rhodamine 6G-labeled leukocyte-endothelial adherence and microvascular permeability to sodium fluorescein in cortical venules. Asphyxia was induced by discontinuing ventilation. SOD and C3 were administered by cortical superfusion. The xanthine oxidase inhibitor oxypurinol was administered intravenously. Results: Leukocyte-venular adherence significantly increased during the initial 2 hours of post-asphyxial reperfusion. BBB permeability was also elevated relative to non-asphyxial controls. Inhibition of O2• production by oxypurinol, or elimination of O2• by SOD or C3, significantly reduced rhodamine 6G-labeled leukocyte-endothelial adherence and improved BBB integrity, as measured by sodium fluorescein leak from cerebral microvessels. Conclusion: Using three different strategies to either prevent formation or enhance elimination of O2• during the post-asphyxial period, we saw both reduced leukocyte adherence and preserved BBB function with treatment. These findings suggest that agents which lower O2• in brain may be attractive new therapeutic interventions for the protection of the neonatal brain following asphyxia.